Effects of Specific Training on the Ability to Deal with Cultural References in Translation - Scott-Tennent, Christopher; González Davies, María (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThe aim of this empirical study (carried out as part of a wider research project – see “Credits” below) was to discover the effects of specifically designed pre-service translator training on the trainees’ ability to deal with cultural references, a text segment type which is widely considered as potentially problematic for the translator. Specifically, we set out to discover any significant differences, as a result of said training, in trainees’ ability to: (a) detect cultural references within a text, (b) provide multiple feasible options (variants) to translate them, (c) evaluate those potential options, and (d) apply reasoning in making a final choice from the options. The rationale and nature of the specific training involved has already been extensively reported in González Davies and Scott-Tennent (2005). In the present article, we focus our attention on reporting and discussing its observed effects. The design of the specific training drew heavily on a previous study on specific translator training in problem-solving, reported in Scott-Tennent et al. (2000) and González Davies et al. (2001).